1991
DOI: 10.1002/bjs.1800780404
|View full text |Cite
|
Sign up to set email alerts
|

Repair and replacement of deep vein valves in the treatment of venous insufficiency

Abstract: Venous insufficiency is a widespread condition, the prevalence of venous ulceration being 0.5-1.0 per cent in Western populations. A principal abnormality causing venous insufficiency is deep venous reflux, usually resulting from post-thrombotic valve destruction. Patients undergoing treatment for venous insufficiency should have all venous abnormalities investigated, defined and corrected where possible. Although treatment for superficial and communicating vein incompetence is available, correction of deep ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…This is supported by previous findings, which have emphasized the importance of the popliteal segment in the pathogenesis of venous ulceration. [17][18][19][20][21][22] Stuart et al 20 studied 233 patients with venous disease and found that a history of open or healed ulceration was strongly associated with reflux in the popliteal vein with 49% of subjects with ulceration having reflux in their popliteal vein compared with only 15% of subjects with varicose veins (P ϭ .002). Welch et al 21 also found that the frequency of reflux in the popliteal vein increased as the clinical symptoms progressed, with a significant increase in class III ulcerated limbs when compared with nonulcerated limbs.…”
Section: Discussionmentioning
confidence: 95%
“…This is supported by previous findings, which have emphasized the importance of the popliteal segment in the pathogenesis of venous ulceration. [17][18][19][20][21][22] Stuart et al 20 studied 233 patients with venous disease and found that a history of open or healed ulceration was strongly associated with reflux in the popliteal vein with 49% of subjects with ulceration having reflux in their popliteal vein compared with only 15% of subjects with varicose veins (P ϭ .002). Welch et al 21 also found that the frequency of reflux in the popliteal vein increased as the clinical symptoms progressed, with a significant increase in class III ulcerated limbs when compared with nonulcerated limbs.…”
Section: Discussionmentioning
confidence: 95%
“…Direct valvuloplasty produces secure cusp apposition without cusp prolapse by shortening the redundant floppy valve cusp edges, while indirect valvuloplasty does so by narrowing the dilated sinus. 5 In the present case, angioscopy-assisted anterior valve sinus plication, a type of indirect valvuloplasty, was performed as previously described. 1 The technique is simple and can be rapidly performed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with deep vein insufficiency and grade 3 -4 regurgitation (assessed using the Kistner classification 20 ) should undergo deep venous valve repair surgery. 34 Patients with previous deep venous thrombosis require careful consideration; treatment selection should be based on the state of blood flow recanalization. Patients with partial recanalization of the occluded vein can undergo conservative therapy and may also be considered for GSV cross transfer.…”
Section: Discussionmentioning
confidence: 99%